Properties of Block Matrices - Dinsev, Şakir Mehmet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
In this master thesis, we study the block matrices and their properties. After giving a general overview on matrices, block matrices, different types of block matrices, and multiplication of two block matrices are discussed. In the inverse section, we first examine inverses of 2×2 block diagonal and block triangular matrices, ideas of proofs here can be extended to a general n × n block diagonal or a block triangular matrix. Then we give the inverse formula for 2 × 2 block matrix, in the case that one of the blocks is invertible. We then generalise this to any n×n block matrix by splitting it into 4 blocks (by producing a 2×2 block matrix). Determinant chapter is covered by two different methods, existing in the literature. First we revise a formulae for determinant of a block matrix where the blocks (matrices) belong to a commutative subring of Mn×n(F), where F is a field or a commutative ring. Then we give the general formula which would work for any block matrix, without any commutativity condition between the blocks. We also present formulas for the determinant of tensor product of two given matrices. Keywords: block matrix, inverses, determinants, tensor products

ÖZ: Bu yüksek lisans tezinde, blok matrisler ve özellikleri incelenmi¸stir. Matrislere genel bir bakı¸s verildikten sonra, blok matrisler, farklı blok matris türleri ve iki blok matrisin çarpımı ele alınmı¸stır. Blok matrislerin tersleri bölümünde, önce 2×2 blok kö¸ segen ve blok üçgensel matrislerin tersi incelenmi¸stir. Buradaki ispat yöntemleri genel bir n×n blok kö¸segen veya blok üçgensel matrisine geni¸sletilebilir. Daha sonra bloklarin herhangi birinin tersinin olması ko¸suluna dayanarak 2 × 2 block matrislerinin terslerinin formülü verilmi¸stir. Ayrıca bu formül n×n blok matrisini 4 tane blo˘ ga bölerek genelle¸stirilebilir (2 × 2 blok matris üreterek). Determinant bölümü, literatürde var olan iki farklı yöntemle ele alınmı¸stır. ˙ Ilk olarak blokların(matrislerin), Mn×n(F)’ nin de˘ gi¸sme özelli˘ gi olan alt-halkasına ait olması durumunda (buradaki F bir cisim veya de˘ gi¸sme özelli˘ gi olan bir halkadır) blok matrisin determinant formülü revize edilmi¸stir. Bunun yanında bloklar arasında herhangi bir de˘ gi¸sme ko¸sulu olmaksızın determinant formülü incelenmi¸stir. Ayrıca verilen iki matrisin tensör çarpımının determinantı formülleri sunulmu¸stur.
Master of Science in Mathematics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2023. Supervisor: Assist. Prof. Dr. Müge Saadetoğlu.
Keywords: Thesis Tez; Mathematics Department; Algebras, Linear--Matrices; Block matrix; inverses; determinants; tensor products